Speech of Kediri Mayor: A Rhetorical Study - Azrilya Agoesta Nur Fatiha; Syamsul Sodiq (Jurnal Pembelajaran Bahasa dan Sastra, 2025)
This study aims to describe the rhetorical structure of the Mayor of Kediri’s speeches based on Monroe’s Motivated Sequence and to identify strategies for character portrayal through the elements of ethos, pathos, and logos in Aristotelian rhetoric. The study was conducted in the Kediri City Government environment with a data collection period from July to October 2025. The research population included the Mayor of Kediri’s speeches from 2023 to 2025, while the sample was purposively selected from five official speeches that met the criteria of complete rhetorical structure and contained the context of public policy and ceremonial events. The research instruments included documentation sheets for selecting and reviewing the speeches, as well as semi-structured interview guidelines used to obtain contextual data from Prokompim staff. The data were analyzed using textual analysis methods through two stages, namely rhetorical structure analysis based on the five stages of Motivated Sequence (attention, need, satisfaction, visualization, action) and character imaging analysis based on Aristotelian rhetoric. The results of the study show that all speech manuscripts consistently apply Monroe’s rhetorical pattern, particularly through the use of an interesting opening, presentation of public issues, policy solutions, visualization of the city’s future, and calls to action. In addition, all speeches present aspects of ethos, pathos, and logos in a balanced manner in building the image of the Mayor as a religious, credible, communicative leader.